2021
DOI: 10.1002/jgc4.1511
|View full text |Cite
|
Sign up to set email alerts
|

Do research participants share genomic screening results with family members?

Abstract: The public health impact of genomic screening can be enhanced by cascade testing. However, cascade testing depends on communication of results to family members. While the barriers and facilitators of family communication have been researched following clinical genetic testing, the factors impacting the dissemination of genomic screening results are unknown. Using the pragmatic Electronic Medical Records and Genomics Network‐3 (eMERGE‐3) study, we explored the reported sharing practices of participants who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…However, majority (77.7%) would not want the results shared directly with their relatives by the doctor/ GC without their permission. Studies exploring willingness to share genetic ndings with relatives have also reported similar general willingness to share the results and forgo one's own con dentiality [23,24]. Moreover, there was a consensus among the respondents for knowing the secondary ndings for treatable as well as untreatable conditions and VUS.…”
Section: Discussionmentioning
confidence: 85%
“…However, majority (77.7%) would not want the results shared directly with their relatives by the doctor/ GC without their permission. Studies exploring willingness to share genetic ndings with relatives have also reported similar general willingness to share the results and forgo one's own con dentiality [23,24]. Moreover, there was a consensus among the respondents for knowing the secondary ndings for treatable as well as untreatable conditions and VUS.…”
Section: Discussionmentioning
confidence: 85%
“…Four additional questionnaires developed or adapted by the study team, including Perceived Utility, Results Congruency, Sharing of Results, and Family Testing (30), are also administered at T4. Perceived Utility measures participants' perceived usefulness of the return of result information and return of result process, while Results Congruency measures whether participants feel the results received match what they were expecting.…”
Section: Sa2 Quantitative Measures: To Resultsmentioning
confidence: 99%
“…Communicating risk estimates properly should also include an adequate knowledge of the limitations of the methodology used to produce them and their discussion with the service users and their families ( Smeland and Andreassen, 2021 ). For example, studies show a need to educate healthcare providers regarding approaches to facilitate sharing of genetic results within families ( Wynn et al, 2021 ). This is particularly pertinent as genetic results may have implications for more than one family member.…”
Section: Communicating Risk Estimates and Understanding Implicationsmentioning
confidence: 99%